A personalized model of real-life space for providing ambient service - Sora Lim; Jong-Gak Choe; Kwon, Yong-Jin (2012 6th International Conference on New Trends in Information Science, Service Science and Data Mining, 2012)
With the advent of a new services environment based on high-speed mobile networks and high-performance mobile devices, users in real life require content-centric services that provide personalized information conveniently and efficiently. These services are defined as ambient services. To implement and support sustainable ambient services, there is a critical need to conduct research regarding practicable models and methodologies. This paper proposes an effective model for ambient services based on the personalization of real-life space. The model consists of Public Info-space, Universal Info-space and Private Info-space. We also show a methodology for implementing the model with currently available techniques in order to prove that the model and methodology constitute an applicable solution to developing true ambient services. Finally, a kind of role-playing game which is built on a real university campus is presented to show the model to be available, where the test bed infrastructure consists of wireless mesh networks and real-time location systems (RTLSes).